Stock price movements does change in energy price matter? - Abdul Jalil Norasibah, Mat Ghani Gairuzazmi, Daud Jarita, Ibrahim Mansor (N/A, 2009)
Stock price movements does change in energy price matter? by Abdul Jalil Norasibah, Mat Ghani Gairuzazmi, Daud Jarita, Ibrahim Mansor,